The associations of religiosity and family atmosphere with lifestyle among Saudi adolescents - Tawfik Mamoun Rajab; Juliann Saquib; Ahmad Mamoun Rajab; Saed Enabi; Saleh Qusai Saleh Ayash; Suhaib Abdelrahman Abdellatif Abdelrahman; Mohammed Abdulaziz Abdulwahab Khojah; Abdulrahman Almazrou; Nazmus Saquib (Elsevier, 2021)
There have been gradual sociocultural changes in Saudi Arabia due to globalization. This allows a unique opportunity to examine religiosity and family atmosphere in relation to lifestyle among Saudi adolescents. In this cross-sectional study, 2067 school students (grades 7-12) from 32 randomly selected schools in Al-Qassim, Saudi Arabia were enrolled. Perceived religiosity, family atmosphere, lifestyle (e.g., physical activity, diet, screen time, obesity, and smoking), demography, parental attributes, and religious practices were assessed with validated scales and questions. A risk profile was created from the lifestyle variables (none, one, two, or ≥ three), and the students were grouped into low versus high religiosity and low versus high family atmosphere using a median split. Multinomial regressions were used to model the lifestyle risk profile. The mean age ±standard deviation was 15.5 years ±1.7, and 35% were girls; 28% had no risk factors, 32% had one, 25% had two, and 15% had ≥3. After adjustment, both low religiosity and low family atmosphere were significant correlates of the lifestyle risk profile (e.g., ≥3 risk factors: religiosity OR = 2.9, 95% CI: 2.1, 4.0; family atmosphere OR = 2.0, 95% CI: 1.5, 2.8). Those with both low religiosity and low family atmosphere were more likely to have a higher lifestyle risk profile than those who scored high in religiosity and better in family atmosphere (e.g., ≥3 risk factors: OR = 5.9, 95% CI: 3.7, 9.5). Hence, higher religiosity and better family atmosphere are associated with less risky lifestyles among Saudi adolescents.